2020
DOI: 10.3390/cancers12113421
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Survival, and Mortality Trends of Cancers Diagnosed in Adolescents and Young Adults (15–39 Years): A Population-Based Study in The Netherlands 1990–2016

Abstract: Adolescent and young adult (AYA) cancer patients, aged 15–39 years at primary cancer diagnosis, form a distinct, understudied, and underserved group in cancer care. This study aimed to assess long-term trends in incidence, survival, and mortality of AYA cancer patients within the Netherlands. Data on all malignant AYA tumours diagnosed between 1990–2016 (n = 95,228) were obtained from the Netherlands Cancer Registry. European age-standardised incidence and mortality rates with average annual percentage change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 81 publications
1
36
1
Order By: Relevance
“…(7) Clustering stopping rule: If |D j+1 − D j | < 0.01, then stop further dividing and clustering. (8) Regarding the determination of number of clusters, we adopted the method proposed by Wang [25], the optimal algorithm will iterate in order to classify factors into different numbers of clusters, calculate the cluster cost (in this study, we used the mean sum of squares within clusters as the cluster cost measurement) and compare the sums of squares between clusters. If the sum of squares of k clusters did not show statistically significant difference from k + 1 clusters, the optimal number of clusters is determined as k.…”
Section: Step 2 K-means Clustering With V-fold Cross-validationmentioning
confidence: 99%
See 2 more Smart Citations
“…(7) Clustering stopping rule: If |D j+1 − D j | < 0.01, then stop further dividing and clustering. (8) Regarding the determination of number of clusters, we adopted the method proposed by Wang [25], the optimal algorithm will iterate in order to classify factors into different numbers of clusters, calculate the cluster cost (in this study, we used the mean sum of squares within clusters as the cluster cost measurement) and compare the sums of squares between clusters. If the sum of squares of k clusters did not show statistically significant difference from k + 1 clusters, the optimal number of clusters is determined as k.…”
Section: Step 2 K-means Clustering With V-fold Cross-validationmentioning
confidence: 99%
“…The economic burden of treatments and care for lung cancer has also globally increased in recent years [ 6 , 7 ]. Published studies have showed that lung cancer is significantly associated with older age (70 years old being the average age of initial diagnosis) [ 7 , 8 ], but very low incidence rate in young people aged 20–40 years around the world [ 8 ]. In recent decades, due to the dramatic improvements of clinical treatments and screening techniques for lung cancer, the survival of newly diagnosed lung cancer patients has been significantly prolonged [ 9 , 10 ] and the incidence rate in young patients with lung cancer also increased [ 1 , 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, melanoma is one of the most common cancers in adolescents and young adults, especially in women. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, population-based cancer registry data have generally shown poorer survival of AYAs compared with children and older adults [ 11 , 12 ]. Nonetheless, more recently, decreases in mortality rates for all AYAs combined were found, although with notable differences by tumor type [ 11 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%